2007
DOI: 10.3317/jraas.2007.021
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin type 1 receptor blockade prevents endocardial dysfunction of rapidly paced atria in rats

Abstract: Paper AbstractIntroduction. Atrial fibrillation (AF) per se causes atrial endocardial dysfunction leading to local coagulation imbalance on the internal surface of the atrium, which contributes to thrombus formation in the fibrillating left atrium. Materials and methods. To test a hypothesis that blockade of angiotensin II type 1 receptor (AT 1 -receptor) prevents the endocardial dysfunction by AF, we examined the effects of olmesartan on the expression of tissue factor pathway inhibitor (TFPI), thrombomodulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The cut-off value of s-TM for AF recurrence was 10.07 U/mL, although specificity and sensitivity were relatively low. In an experimental rat model, rapid atrial pacing downregulated the gene expression of TM in atrial endocardium, 40 suggesting that the AF condition downregulated TM expression in the heart or endothelial cells and decreased serum s-TM.…”
Section: Discussionmentioning
confidence: 99%
“…The cut-off value of s-TM for AF recurrence was 10.07 U/mL, although specificity and sensitivity were relatively low. In an experimental rat model, rapid atrial pacing downregulated the gene expression of TM in atrial endocardium, 40 suggesting that the AF condition downregulated TM expression in the heart or endothelial cells and decreased serum s-TM.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the LA enlargement may be a surrogate marker representing an adaptive response to some variously caused endothelial dysfunction that affects the systemic vascular bed. Endothelial dysfunction results from the abnormal regulation of and response to many different cytokines and paracrine hormones, including nitric oxide, angiotensin II and its receptor, plasminogen nhibitor I, thrombomodulin, and endothelin [ 19 ]. In particular, angiotensin II and its receptor are well-known 30 The Korean Journal of Internal Medicine Vol.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 This hypothesis is supported by a recently published report that indicated that angiotensin II receptor blockers could partially prevent atrial endothelial dysfunction and the occurrence of AF. 27,28 Apparently, intravascular thrombotic events in patients without AF are generally associated with abnormalities in vascular endothelial functioning and/or the coagulation system. In patients with pAF, endothelial dysfunction may also play an important role in thrombogenesis in the LA.…”
Section: Discussionmentioning
confidence: 99%